Auxetic Materials and Structures - Lim, Teik-Cheng (Engineering Materials, 2015)
This book describes the fundamentals of the mechanics and design of auxetic solids and structures, which possess a negative Poisson's ratio. It will benefit two groups of readers: (a) industry practitioners, such as product and structural designers, who need to control mechanical stress distributions using auxetic materials, and (b) academic researchers and students who intend to produce structures with unique mechanical and other physical properties using auxetic materials.